Electrolyte for constructing stable interface of zinc-based battery and application
By using sodium naphthalene disulfonate as additive electrolyte in zinc-based batteries, a stable interface is constructed, and the problem of poor stability of zinc-based batteries in a wide pH range is solved, and the cycle reversibility and life are improved.
Patent Information
- Application Number
- CN202411951078.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-25
AI Technical Summary
Zinc-based batteries have problems in the generation of dendrites, hydrogen evolution reaction, chemical/electrochemical corrosion and passivation in a water-electrolyte environment with a wide pH range, resulting in poor stability, low utilization and short cycle life of zinc anode.
An electrolyte containing a sodium naphthalene disulfonate salt as an additive is used to form a stable interface through its adsorption on the zinc-based surface, guiding preferential deposition of zinc ions along the orientation of (002), thereby inhibiting the growth of dendrites.
Effectively build a stable interface, inhibit aquatic side reactions and disordered growth of dendrites, and improve the cyclic reversibility and life of zinc-based batteries under high current and high capacity conditions.
Smart Images

Figure CN119890480A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of electrolyte for zinc-based batteries, and in particular to an electrolyte for constructing a stable interface of a zinc-based battery and its application. Background Art
[0002] The high manufacturing cost and serious safety issues of lithium-based batteries limit their large-scale application, so the development of alternative battery technologies is at the forefront of research. In recent years, rechargeable aqueous zinc metal batteries (AZMBs) have been considered as commercial candidates for off-grid energy storage due to their superior environmental compatibility, inherent safety, high crustal abundance of zinc raw materials, and cost-effectiveness. Due to their suitable redox potential (-0.76 V vs standard hydrogen electrode, SHE), high theoretical specific capacity (820 mAh g −1 ,5855 mAh cm −3 ) and high electrical conductivity, zinc metal has been recognized as one of the most promising anode materials for AZMB systems.
[0003] However, the generation of dendrites, hydrogen evolution reaction (HER), chemical / electrochemical corrosion, and passivation seriously reduce the stability of zinc metal anodes in aqueous electrolyte environments with a wide pH range. In mildly acidic and alkaline electrolytes, needle-shaped dendrites are usually generated at sites with high local Zn concentrations due to the formation of concentration gradients. The generation of dendrites not only reduces the utilization of the zinc anode, but also provides more reaction sites for chemical corrosion and HER. So far, many methods have been devoted to solving this challenging problem, such as electrolyte regulation, artificial interface, and zinc anode structure design. Among them, the construction of artificial interface can directly hinder water molecules from entering the interface and can guide the deposition of zinc ions. However, there are still complex processes, and they will fall off and fail due to volume changes during long-term cycles. Therefore, they cannot operate normally under high current density and high capacity conditions, which greatly limits their use in practical applications. The high cost of zinc anode structure design makes industrialization unlikely. Electrolyte regulation has attracted much attention due to its advantages of simple operation, low cost, and significant effect.
[0004] Electrolyte regulation can be divided into two categories: one is to regulate the solvation structure of zinc ions, and the other is to regulate the deposition behavior of zinc ions by in-situ construction of a stable interface. Although the behavior of additive molecules participating in the solvation sheath structure inhibits the occurrence of aquatic reactions to a certain extent, it will seriously slow down the desolvation progress of hydrated zinc ions at the interface, thereby affecting the performance of the battery at high current density. Therefore, the design of a stable interface electrolyte for zinc-based batteries is urgently needed in the field of realizing high-performance zinc-based batteries. A stable interface can induce uniform deposition of zinc ions and inhibit the occurrence of side reactions such as corrosion and hydrogen evolution, thereby optimizing the deposition / stripping kinetics.
[0005] Based on this, it is necessary to design an electrolyte that can build a stable interface on the surface of zinc-based batteries. Summary of the invention
[0006] In order to address the deficiencies in the prior art, the present invention provides an electrolyte for constructing a stable interface for a zinc-based battery and its application. The electrolyte can form an adsorption layer on the surface of a metal negative electrode, guide zinc ions to preferentially deposit along the (002) orientation, thereby inhibiting the growth of dendrites and ultimately stabilizing the interface of the zinc-based battery.
[0007] In order to achieve the above object, the specific scheme adopted by the present invention is: On the one hand, the present invention provides an electrolyte for constructing a stable interface of a zinc-based battery, comprising a soluble zinc salt, a solvent and an additive, wherein the additive is sodium naphthalene disulfonate, and the substitution sites of two sulfonic acid groups on the naphthalene ring in the sodium naphthalene disulfonate are rotationally symmetric or axially symmetric.
[0008] Furthermore, the additive is any one of 2,6-naphthalene disulfonate, 1,5-naphthalene disulfonate, and 2,7-naphthalene disulfonate.
[0009] Furthermore, the additive is sodium 2,6-naphthalene disulfonate.
[0010] Furthermore, the concentration of the additive in the electrolyte is 0.25~10 g / L.
[0011] Furthermore, the concentration of the additive in the electrolyte is 1 g / L.
[0012] Furthermore, the soluble zinc salt is ZnX j , where X is Cl - Br - ,I - 、SO 4 2- CF 3 SO 3 - 、NO 3 - In any of the above, the value of j is determined by the valence of X.
[0013] Furthermore, the zinc-based battery is an aqueous zinc-ion battery, a zinc-bromine flow battery, a zinc metal battery, or a battery system using Zn metal as an electrode.
[0014] The invention discloses an electrolyte for constructing a stable interface of a zinc-based battery and its application in the field of zinc-based batteries.
[0015] Beneficial effects: (1) The present invention adds sodium naphthalene disulfonic acid salt as an additive to the electrolyte. The additive is a symmetrical, large sterically hindered interface adsorption molecule that can effectively avoid the hydrogen evolution reaction of water on the interface by adsorbing on the zinc-based surface, and effectively guide the orderly deposition of zinc ions on the interface. Therefore, the constructed stable interface can effectively avoid aquatic side reactions and disordered growth of dendrites, thereby improving the cycle reversibility and life of zinc-based batteries under high current and high capacity conditions.
[0016] (2) The present invention compares the effects of sodium naphthalene disulfonate salts with different position substituents on the performance of zinc-based batteries, which highlights the effect of steric hindrance on the deposition behavior of zinc ions. It is verified through experiments that the stable interface constructed by the 2,6-sodium naphthalene disulfonate additive can make the zinc ion deposition more stable and reversible, while inhibiting the occurrence of hydrogen evolution and corrosion, and ultimately achieving higher cycle stability.
[0017] (3) The electrolyte additive provided by the present invention can construct a stable interface on the surface of the zinc electrode, providing more "channels" for effective nucleation sites and guiding Zn 2+ The nanostructured carbon atoms are uniformly distributed and deposited on the interface. The dense interface can further hinder water molecules from entering the interface, thereby reducing the occurrence of interfacial side reactions.
[0018] (4) The electrolyte of the present invention has the advantages of low price, safety, and wide application. It can solve the problems of serious interfacial byproducts and difficult-to-control zinc dendrites faced by current zinc-based batteries, and has the application prospect of achieving long cycle life and high cycle stability. This invention is expected to improve the commercial application potential of zinc-based batteries in the field of energy storage and provide new ideas and new directions for electrolyte design. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 Schematic diagram of the substitution site of the naphthalene ring in the present invention.
[0020] Figure 2 Cycling performance test results of symmetrical batteries assembled with the electrolyte provided in Example 1 and the electrolyte provided in Comparative Example 1.
[0021] Figure 3 The cycle performance test results of the symmetrical battery assembled with the electrolyte provided in Example 2.
[0022] Figure 4 The cycle performance test results of the symmetrical battery assembled with the electrolyte provided in Example 3.
[0023] Figure 5 The cycle performance test results of the symmetrical battery assembled with the electrolyte provided in Example 4.
[0024] Figure 6The cycle performance test results of the symmetrical battery assembled with the electrolyte provided in Example 5.
[0025] Figure 7 The zinc negative electrode of the symmetrical battery assembled with the electrolyte provided in Example 1 and Comparative Example 1 was -2 , area capacity of 1 mA cm -2 SEM images of 50 cycles under the same conditions.
[0026] Figure 8 The zinc negative electrode of the asymmetric battery assembled with the electrolyte provided by Example 1 and Comparative Example 1 was -2 , area capacity of 1 mA cm -2 SEM images of 50 cycles under the same conditions. DETAILED DESCRIPTION
[0027] The technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0028] The present invention provides an electrolyte for constructing a stable interface of a zinc-based battery, which is used in the field of zinc-based batteries and includes a soluble zinc salt, a solvent and an additive, wherein the additive is sodium naphthalene disulfonate. The selected additive has different effects on the zinc electrode due to different positions of the substitution groups and different steric hindrances. The substitution positions of naphthalene are as follows: Figure 1 The additive is any one of 2,6-naphthalene disulfonate, 1,5-naphthalene disulfonate and 2,7-naphthalene disulfonate, that is, the substitution sites of the two sulfonic acid groups on the naphthalene ring are rotationally symmetric or axially symmetric.
[0029] Among them, the concentration of the additive in the electrolyte is 0.25~10 g / L.
[0030] It should be noted that the soluble zinc salt is ZnX j , where X is Cl - Br - ,I - 、SO 4 2- CF 3 SO 3 - 、NO 3 - In any of the above, the value of j is determined by the valence of X.
[0031] Zinc-based batteries are aqueous zinc-ion batteries, zinc-bromine flow batteries, zinc metal batteries, or battery systems with Zn metal as electrodes.
[0032] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods.
[0033] The reagents and materials used in the following examples can be obtained from commercial sources.
[0034] Example 1 The preparation method of the electrolyte for zinc-based battery comprises the following steps: Step 1: Weigh 28.755 g of zinc sulfate heptahydrate powder and place it in an 80 ml orange-capped bottle to prepare a 2 M zinc sulfate solution; Step 2: Weigh 0.025 g of sodium 2,6-naphthalene disulfonate powder, pour it into the orange-capped bottle in (1), and add 37.4 ml of deionized water with a resistance of 18.25 MΩ; Step 3: Ultrasonicate for 30 min to completely dissolve and mix evenly, and finally obtain 50 ml of clear and transparent electrolyte, in which the concentration of sodium 2,6-naphthalene disulfonate is 0.5 g / L.
[0035] Example 2 The difference between Example 2 and Example 1 is that: (1) in step 2, the amount of sodium 2,6-naphthalene disulfonate powder added is 0.05 g; and (2) in step 3, the concentration of sodium 2,6-naphthalene disulfonate in the electrolyte is 1 g / L.
[0036] Example 3 The difference between Example 3 and Example 1 is that: (1) in step 2, the amount of sodium 2,6-naphthalene disulfonate powder added is 0.1 g; and (2) in step 3, the concentration of sodium 2,6-naphthalene disulfonate in the electrolyte is 2 g / L.
[0037] Example 4 The difference between Example 4 and Example 2 is that: (1) in step 2, sodium 1,5-naphthalene disulfonate powder is added.
[0038] Example 5 The difference between Example 5 and Example 2 is that: (1) in step 2, sodium 2,7-naphthalene disulfonate powder is added.
[0039] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that step 2 is not included, that is, no additive is added.
[0040] (1) Cycle performance analysis The zinc foil was placed in the positive electrode shell, followed by the glass fiber separator, the zinc negative electrode, and the stainless steel gasket. The electrolyte prepared in Examples 1-5 and Comparative Example 1 was dripped until the separator was completely wetted, and then the negative electrode shell was pressed into place. Finally, the battery was sealed in a packaging machine to obtain a symmetrical battery. The assembled button battery was tested for cycle performance using the Xinwei electrochemical test system. The cycle conditions were: current density 1 mA cm -2 , with an area capacity of 1 mA cm -2 Please refer to Figure 2 Compared with Comparative Example 1, it can be seen that the symmetrical battery without additives suffers from the problem of uncontrollable growth of dendrites and short-circuits in less than 60 hours, indicating that the uneven deposition at the interface is aggravated by the side reaction. The growth of dendrites will cause the battery to short-circuit, thereby greatly shortening the battery life. The electrolyte obtained in Example 1 (sodium 2,6-naphthalene disulfonate concentration of 0.5 g / L) shows excellent cycle stability during cycling and greatly prolongs the cycle life of the battery, which can work stably for more than 800 hours. Please refer to Figure 3 The electrolyte obtained in Example 2 (sodium 2,6-naphthalene disulfonate concentration of 1 g / L) exhibited excellent cycle stability during cycling and greatly prolonged the cycle life of the battery, and could work stably for more than 3500 h. This indicates that the stable interface constructed by the 1 g / L sodium 2,6-naphthalene disulfonate additive can inhibit the occurrence of hydrogen evolution and corrosion, and improve the cycle life and tolerance of the symmetrical battery. Please refer to Figure 4 The electrolyte obtained in Example 3 (2,6-naphthalene disulfonate concentration of 2 g / L) can prolong the cycle time during cycling, but it can only cycle for 200 h. This may be due to the fact that the addition of too much bulky steric additives will hinder the deposition of zinc ions. It can be seen that the optimal addition concentration of 2,6-naphthalene disulfonate additive is 1 g / L. Therefore, when discussing the effect of different site substitutions on battery performance in the future, the preferred concentration is 1 g / L to compare the effect of different site substitutions on zinc ion deposition behavior. Please refer to Figure 5 The battery assembled with the electrolyte obtained in Example 4 (the concentration of 1,5-naphthalene disulfonate sodium is 1 g / L) exhibits more stable voltage polarization and longer life than that in Comparative Example 1, but the life is significantly lower than that in Example 2. This may be related to the fact that the sulfonic acid group replaces the 1 and 5 sites of naphthalene, which will cause greater steric hindrance and further hinder the transport behavior of zinc ions. Please refer to Figure 6 The battery assembled with the electrolyte obtained in Example 5 (the concentration of sodium 2,7-naphthalene disulfonate is 1 g / L) can only cycle for 120 hours. Although the performance is better than that of the battery without additives, the life is significantly lower than that of Example 2. This may be related to the fact that the sulfonic acid group replaces the 2 and 7 sites of naphthalene, which further hinders the transmission behavior of zinc ions. Figures 2 to 6It can be seen that the stable interface constructed by the sodium 2,6-naphthalene disulfonate additive can make the zinc ion deposition more stable and reversible, while inhibiting the occurrence of hydrogen evolution and corrosion, and ultimately achieving higher cycle stability.
[0041] (2) Characterization and mechanism analysis of the zinc anode after cycling Symmetrical battery assembly and testing: Zinc sheets were used as positive and negative electrodes, glass fiber was used as separator, and zinc sulfate electrolyte with and without nicotinic acid additive was added to assemble the symmetric battery. The obtained symmetric battery was electrochemically cycled using an electrochemical test system. The cycle conditions were: current density 1 mA cm -2 , with an area capacity of 1 mA cm -2 The number of cycles was 30. After the cycle was completed, the button battery was disassembled, the zinc foil on the reduction side after discharge was selected and the diaphragm on the surface was removed with tweezers, and then placed in an ethanol culture dish and ultrasonicated for 10 s to remove the residual electrolyte on the surface, and the ethanol on the surface was dried with a hair dryer.
[0042] Firstly, scanning electron microscopy was used to analyze the surface morphology of the zinc foil. Figure 7 High-magnification scanning electron microscope (SEM) images of the surface of the zinc foil after 50 cycles in the electrolytes of Example 2 and Comparative Example 1. Figure 7 (a) is the surface morphology of the zinc foil disassembled from the symmetrical battery assembled in Comparative Example 1. The zinc negative electrode with an electrolyte of 2 mol / L zinc sulfate is covered with disordered zinc flakes and loose and porous byproducts, which further aggravates the unevenness of the interface and promotes the subsequent growth of dendrites, leading to a short circuit in the battery. Figure 7 (b) It can be seen that the zinc negative electrode of the zinc sulfate electrolyte containing 1 g / L 2,6-naphthalene disulfonic acid sodium salt has uniformly oriented hexagonal zinc sheets, which preferentially form a uniform and dense coating. This indicates that 2,6-naphthalene disulfonic acid sodium salt induces the trend of zinc layered deposition on the (002) crystal plane, thereby improving the electrochemical performance.
[0043] Assembly and testing of asymmetric cells: Replace the positive zinc foil with copper foil and assemble the Zn||Cu half-cell with zinc sulfate electrolyte without / with sodium 2,6-naphthalene disulfonic acid additive according to the assembly method of symmetric cells. -2 , with an area capacity of 1 mA cm -2 The number of cycles was 50 under the condition of . After the cycle was completed, the button battery was disassembled, the zinc foil on the reduction side after discharge was selected and the diaphragm on the surface was removed with tweezers, and then placed in an ethanol culture dish and ultrasonicated for 10 s to remove the residual electrolyte on the surface, and the ethanol on the surface was dried with a hair dryer.
[0044] Results and analysis: Figure 8As shown in Fig. 1, the copper substrate assembled by the electrolyte of Comparative Example 1 exhibits a loose and porous zinc deposition phenomenon, and this morphology proves that the deposition of zinc on the copper substrate is not tight. This also proves the serious hydrogen evolution reaction and corrosion phenomenon, because the loose zinc comes from the unevenness and voids caused by corrosion and blistering. The electrolyte added to Example 2 exhibits a tight zinc deposition behavior, which further proves that sodium 2,6-naphthalene disulfonate can improve the reversibility of zinc deposition on copper and reduce the occurrence of side reactions.
[0045] In summary, the multifunctional electrolyte design prepared by the present invention has considerable research value and prospects. The highly symmetrical sodium naphthalene disulfonic acid salt exhibits excellent stabilization of the interface and improves the battery cycle life. This type of additive can be used to stabilize the negative electrode interface of other zinc-based batteries, which can significantly inhibit the deterioration of side reactions and dendrites, and has excellent performance.
[0046] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any equivalent changes or modifications made according to the essence of the present invention should be included in the protection scope of the present invention.
Claims
1. An electrolyte for constructing a stable interface of a zinc-based battery, characterized in that: The invention comprises a soluble zinc salt, a solvent and an additive, wherein the additive is a sodium naphthalene disulfonate salt, and the substitution sites of two sulfonic acid groups on the naphthalene ring in the sodium naphthalene disulfonate salt are rotationally symmetric or axially symmetric.
2. The electrolyte for constructing a stable interface of a zinc-based battery according to claim 1, characterized in that: The additive is any one of 2,6-naphthalene disulfonate, 1,5-naphthalene disulfonate and 2,7-naphthalene disulfonate.
3. The electrolyte for constructing a stable interface of a zinc-based battery according to claim 2, characterized in that: The additive is sodium 2,6-naphthalene disulfonate.
4. The electrolyte for constructing a stable interface of a zinc-based battery according to claim 1, characterized in that: The concentration of the additive in the electrolyte is 0.25~10 g / L.
5. The electrolyte for constructing a stable interface of a zinc-based battery according to claim 1, characterized in that: The concentration of the additive in the electrolyte was 1 g / L.
6. The electrolyte for constructing a stable interface of a zinc-based battery according to claim 1, characterized in that: The soluble zinc salt is ZnX j , where X is Cl - Br - ,I - 、SO4 2- CF3SO3 - 、NO3 - In any of the above, the value of j is determined by the valence of X.
7. The electrolyte for constructing a stable interface of a zinc-based battery according to claim 1, characterized in that: Zinc-based batteries are aqueous zinc-ion batteries, zinc-bromine flow batteries, zinc metal batteries, or battery systems with Zn metal as electrodes.
8. Use of the electrolyte for constructing a stable interface of a zinc-based battery according to any one of claims 1 to 7 in the field of zinc-based batteries.